An interdisciplinary management of severe facial asymmetry due to hemifacial microsomia - Mary Sanjana; Sivakami Manikandan; Uma Maheshwari; Ratna Parameswaran; Devaki Vijayalakshmi (Contemporary Clinical Dentistry, 2020)
This case report outlines the importance of an interdisciplinary approach and a patient centric outcome for the treatment of facial asymmetry resulting from hemifacial microsomia. Different treatment modalities are available to treat asymmetries. However, the best treatment outcome can be achieved only when the treatment plan is individualized for every patient. This report portrays an adult patient with hemifacial microsomia, who had facial asymmetry from the level of supraorbital region with a Class II skeletal base. Orthodontic treatment, along with surgical management, was required to transform the patient into a symmetrical profile, which is esthetically pleasing. A sound knowledge of the various technologies and resources that are available to us and making the best use of it to bring out a drastic change in the patient's life. Combined effort of the orthodontists and oral surgeons are required to manage patient's with hemifacial microsomia that has caused the severe facial asymmetry. Moreover, special attention has to be given to a patient-centric outcome.